The Effect Of Eye Gysing On Complaints Computer Vision Syndrome Impact Of Online Learning - Kurniawati, Ratna Dian; Rosdianah, Lilis; Sutriyawan, Agung (Program Studi Magister Ergonomi Fisiologi Kerja Pascasarjana Universitas Udayana Denpasar Bekerjasama dengan Perhimpunan Ergonomi Indonesia (PEI), 2022)
Computer Vision Syndrome (CVS) was a collection of complaints that are felt by the eye. The current pandemic requires all students to study at home using cellphones/laptops to facilitate the learning process. The results of a preliminary study conducted at MAN 1 Bandung, there were 8 out of 10 students who experienced complaints such as sore eyes, tired eyes and headaches. Efforts to reduce complaints can be done with eye exercises. The purpose of the study was to determine the effect of eye exercise on CVS complaints due to online learning in class XI MAN 1 Bandung. This study was a quasi-experimental study with a non-equivalent control group design with a population of 261 students and a sample of 29 experimental respondents and 28 control respondents. The results of the Wilcoxon test on the score of CVS complaints before and after the intervention was given to the experimental class showed a p-value of 0.000 <? 0.05, so H0 was rejected. And the results of the Mann Whitney test of 0.040 <? 0.05, it can be concluded that there is an effect of eye exercise on CVS complaints in students. It is expected that students can practice eye exercises regularly in order to reduce complaints